Pengaruh model pembelajaran problem based learning berbasis socio scientific issue (Ssi) terhadap computational thinking siswa kelas 5 sd se- kecamatan laweyan - Ilham Malik Akbar; Roy Ardiansyah (Didaktika Dwija Indria, 2025)
The purpose of this study is to investigate how the problem-based learning model based on socio scientific issues affects the Computational thinking skills of fifth-grade elementary school students in Laweyan District, Surakarta. The research used a quantitative experimental methodology, collecting data via essay tests and analyzing the results with the Independent Sample T-test, N-Gain test, and Effect Size test.  A significance value (2-tailed) of 0.001 < 0.05 was found in the analysis results, indicating a significant difference between the experimental and control populations.  The experimental class had an N-Gain value of 0.49 (middle category), whereas the control class had a score of 0.30 (low category). Furthermore, the effect size value in the control class was 1.43 and in the experimental class 3.41, both categorized as large, but the experimental class showed a higher value. Thus, this study demonstrates that problem-based learning based on socio scientific issues is effective in supporting the development of 21st-century skills, particularly Computational thinking.